2019
DOI: 10.1016/j.bpj.2018.11.3135
|View full text |Cite
|
Sign up to set email alerts
|

The Affinity of Sterols for Different Phospholipid Classes and Its Impact on Lateral Segregation

Abstract: Cholesterol is an essential molecule in the membranes of mammalian cells. It is known to be distributed heterogeneously within the cells, between the bilayer leaflets, as well as between lateral domains within the bilayer. However, we do not know exactly how cholesterol is distributed and what forces drive this sorting process because it extremely difficult to study using currently available methods. To further elucidate this distribution, we measured how cholesterol partitions between different phospholipid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 67 publications
7
31
0
Order By: Relevance
“…These interactions are driven by van der Waals contacts, hydrogen bonds, and the shielding of the apolar sterol rings from water by the polar head groups of the phospholipids, a hydrophobic effect 19,20 . The absolute affinities of different membrane phospholipids for cholesterol are not known, but it has been shown that they vary over about an order of magnitude 2,21‐24 . Their complexes have stoichiometries that range from 1:1 for high‐affinity (long chain, saturated) species to two phospholipids per cholesterol for less avid lipids 3,18,20,23,25 .…”
Section: Cholesterol Complexes With Phospholipidsmentioning
confidence: 99%
“…These interactions are driven by van der Waals contacts, hydrogen bonds, and the shielding of the apolar sterol rings from water by the polar head groups of the phospholipids, a hydrophobic effect 19,20 . The absolute affinities of different membrane phospholipids for cholesterol are not known, but it has been shown that they vary over about an order of magnitude 2,21‐24 . Their complexes have stoichiometries that range from 1:1 for high‐affinity (long chain, saturated) species to two phospholipids per cholesterol for less avid lipids 3,18,20,23,25 .…”
Section: Cholesterol Complexes With Phospholipidsmentioning
confidence: 99%
“…Segregation of lipid into lateral domains is a process that seems to be driven by many different forces (10,17,18,59). One factor that has been observed to influence the formation of ordered domains in the membrane plane is the interactions between cholesterol and the different phospholipids present (9,10). An increased relative affinity of cholesterol for the saturated phospholipids, as compared to the unsaturated phospholipids, has been observed to decrease the solubility of PSM in the L d phase and thereby promote the formation of ordered domains.…”
Section: Lateral Segregationmentioning
confidence: 99%
“…Among the saturated phospholipids, cholesterol further seems to have an especially strong affinity for sphingomyelin (6)(7)(8). In bilayers composed of different phospholipids, the presence of cholesterol may influence the lateral organization in the membrane by interacting preferentially with saturated lipids such as sphingomyelin (9)(10)(11). This may lead to the formation of L o domains.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to the umbrella model [99], phospholipid head groups in the membrane shield nonpolar cholesterol bodies from the aqueous phase. PS with a large headgroup has a higher affinity for cholesterol than other phospholipids [48, 101]. Therefore, ergosterol, which is also enriched in the cytoplasmic leaflet [102], loses favorable interacting partners in the triple mutant.…”
Section: Discussionmentioning
confidence: 99%